Analyzing Drug Utilization in Ophthalmology Outpatients in a Private and Public Health Facility as well as Cost Variation of Selected Ophthalmological Medicines - Shivgunde, Prashant P; Kodilkar, Archana D (Journal of Pharmacy Practice and Community Medicine)
Background: The rationale behind this study conduction was; 1. To analyze ‘drug use’ and 2. To analyze ‘cost variation’. First could facilitate improving drug utilization patterns and prescribing practice, and second, could justify and improve rational drug utilization. Materials and Methods: This study was a descriptive, cross-sectional study. Selected ‘World Health Organization’ drug use indicators and cost variation of ophthalmological medicines were analyzed from ‘prospectively collected patient and, prescription data’ and ‘basic cost data of medicines from Current Index of Medical Specialties’, respectively. A total of the ‘449’ patients’ data were considered in the study, out of which ‘231’ and, ‘218’ were from ‘public’ and, ‘private’ health facilities respectively. Results: Out of the total sample, ‘1.36’ was the count of drugs per prescription. The ‘drug percentage’ prescribed by generic name and, from the Essential Medicines List was 31.59% and, 56.35%, respectively. 75.72% of prescriptions were prescribed antibiotics, while 82.41% of patients had correct knowledge of dosage. ‘Eye strain’, ‘conjunctivitis’ and, ‘cataract’ were the common eye problems. ‘Antibiotics’, ‘corticosteroid’ and, ‘ocular lubricants’ were commonly prescribed. From the total of ‘614’ drugs prescribed, ‘171’ was the combination formulations. The study showed high-cost variation among multiple available branded options of single ophthalmological medicine. Conclusion: A rational drug use pattern was found in both the study sites. However, there is a wide variation of the indicators values between them. It is recommended to improve and, periodically update healthcare drug policies along with frequent drug utilization and cost monitoring studies.
Keywords: Drug Utilization (DU); Cost Analysis; Drug Use Indicator; Ophthalmological Medicines; Ophthalmology Outpatient; Essential Medicines; World Health Orgnization (WHO)